Green lantern : first flight [videorecording (DVD)] - Meloni, Christopher; Garber, Victor; Helfer, Tricia; Madsen, Michael; Larroquette, John; Montgomery, Lauren (Warner Home Video, 2009)
When Hal Jordan becomes a Green Lantern, he is put under the supervision of senior Lantern, Sinestro, only to discover that his so-called mentor is part of a secret conspiracy that threatens the entire Green Lantern Corps.